Roteiro para implementação e testes de sistema de comunicação privado entre matriz e filiais - Stadler, Emerson Luiz (2014)
This design was created to remedy failures in new implementations of telephone systems, and configuration errors in installed equipment. The study aims to improve the specific setting methods, which reduces cost and time in the process. The goal is to produce a set of simple activities and easy to understand so it can be used on a daily basis by technicians who are responsible for new installations and require practical information to make the settings. The methodology used to create the script was descriptive, based on a project model that aims to meet a company with four service centers. In addition to targeting quality in the process, PDCA technique was used to improve throughout the implementation. The script developed sought a solution for the process of telephone exchanges settings with interconnections parameters between headquarters and subsidiaries, where a case study was presented that involves the four facilities, they need means of integrated and quick communication.